Step
*
2
1
1
1
1
1
of Lemma
rexp-positive
1. y : ℝ
2. z : ℝ
3. r0 ≤ z
4. r0 ≤ (z + y)
5. r1 ≤ e^z
6. r0 < e^z
7. y = ((z + y) + -(z))
8. r1 ≤ e^z + y
9. r1 = (e^-(z) * e^z)
⊢ r0 < (e^z + y * e^-(z))
BY
{ (nRMul ⌜e^z⌝ 0⋅ THEN (RWO "-1<" 0 THENA Auto)) }
1
1. y : ℝ
2. z : ℝ
3. r0 ≤ z
4. r0 ≤ (z + y)
5. r1 ≤ e^z
6. r0 < e^z
7. y = ((z + y) + -(z))
8. r1 ≤ e^z + y
9. r1 = (e^-(z) * e^z)
⊢ r0 < (e^y + z * r1)
Latex:
Latex:
1.  y  :  \mBbbR{}
2.  z  :  \mBbbR{}
3.  r0  \mleq{}  z
4.  r0  \mleq{}  (z  +  y)
5.  r1  \mleq{}  e\^{}z
6.  r0  <  e\^{}z
7.  y  =  ((z  +  y)  +  -(z))
8.  r1  \mleq{}  e\^{}z  +  y
9.  r1  =  (e\^{}-(z)  *  e\^{}z)
\mvdash{}  r0  <  (e\^{}z  +  y  *  e\^{}-(z))
By
Latex:
(nRMul  \mkleeneopen{}e\^{}z\mkleeneclose{}  0\mcdot{}  THEN  (RWO  "-1<"  0  THENA  Auto))
Home
Index